Comparative study between 25 µg vaginal misoprostol and PGE2 gel for induction of labour at term - Mishra, Ritika; Shinde, Suhas; Gavali, Urmila; Aher, Gautam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Labour induction is a critical aspect of obstetric care, significantly affecting maternal and neonatal outcomes. Prostaglandins such as PGE2 gel facilitate cervical ripening and uterine contractions. Misoprostol, a prostaglandin E1 analogue, has shown promising results in achieving vaginal delivery within 24 hours. This study aims to compare these agents to provide clearer guidance on the safer and more effective option for labour induction. To compare the effectiveness and safety of 25 μg vaginal misoprostol versus 0.5 mg PGE2 gel for induction of labour at or beyond 37 weeks of gestation in terms of efficacy, foeto-maternal outcomes, and complications. Objectives include comparing induction-to-delivery intervals, caesarean rates, and foeto-maternal outcomes between the two drugs. Methods: A single-centre, randomised, open-label clinical trial was conducted in a tertiary care centre’s Obstetrics and Gynaecology department. A total of 176 women were randomised: Group A received 25 μg misoprostol every 4 hours (up to five doses), and Group B received 0.5 mg PGE2 gel every 6 hours (up to three doses). Outcomes included induction-to-delivery time, labour onset, need for augmentation, and maternal and neonatal outcomes. Results: Both groups were similar in age, parity, and Bishop scores. Misoprostol led to quicker labour onset (6.5 vs. 8.5 hours) and required less oxytocin (15.9% vs. 45.5%). Delivery mode and neonatal outcomes were comparable. Conclusions: Misoprostol proved more effective, with shorter induction-to-delivery intervals and less need for augmentation. It is cost-effective, stable at room temperature and offers similar maternal and neonatal safety compared to PGE2 gel.